Mutação constitucional, entre a interpretação e a Justiça Constitucional - Cortucci, Andréa Mancine (2016)
The present dissertation, based on the fact that the Constitution is in a constant dialectical process with the reality underlying it, reflects on the mutability of constitutional norms, especially in view of the numerous formal reforms (constitutional amendments) of the brazilian Constitution which are responsible not only for its desprestige, but also for the weakening of its normative force. This reflection is important for the understanding of the informal mechanisms of change of the Constitution (constitutional mutations), especially those promoted through interpretation, as the adequate and privileged way to adapt the current brazilian Constitution to the fact-concrete dynamics, guaranteeing its relevance in today's world. Assuming hermeneutic references, mainly Hans-Georg GADAMER's philosophical hermeneutics and Ronald DWORKIN's theory of constructive legal interpretation, parameters are defined to the constitutional mutation consistent with the preservation of normative force and constitutional integrity. It is demonstrated with this, within the parameterization of the phenomenon, that the interpretation of the Constitution, although exercised to update it, is not rooted in the discretion of its many different interpreters, especially its final interpreter, the Constitutional Court. It is also proposed to understand the newly acquired role of the Constitutional Court - and the objections that accompany it - in the contemporary constitutional reality and its relation to constitutional mutations. Once the traditional criticisms of the judicial institution (offense to the democratic principle, violation of Parliament's sovereignty and breach of the separation of Powers) have been dismantled and the procedural and substantive dimensions of its functional performance have been explored, it remains clear that the active and substantive role of Constitutional Court, based on the mutational interpretation of the constitutional norm, is the appropriate way to alleviate the serious differences and deficiencies still manifested in the brazilian social sphere